REALIZING THE FOUR PILLARS OF EDUCATION IN DEVELOPING STUDENT CHARACTER AT NASYATUL AISYIYAH MUNGKA KINDERGARTEN LEVEL - Maryelliwati Maryelliwati; Harizqi Azri; Hari Adi Rahmad; Wahyudi Rahmat; Refa Lina Tiawati; Rival Yuhendri (Universitas PGRI Sumatera Barat, 2023)
The present and forthcoming educational requirements are focused on enhancing the calibre of cognitive competencies and expertise, in addition to the attitudes, character, and ethics of the Indonesian populace as a whole, to realize the national educational objectives. Early childhood education plays a crucial role in shaping the creative, adaptive, and commendable character of students, thereby contributing significantly to the attainment of national education objectives. Educators hold a significant position in the educational journey of students, particularly in primary education, as they provide guidance and support throughout the learning process. The primary duty of a teacher, as a professional educator, is to instruct, guide, and mentor students towards the development of refined, self-sufficient, and exceptional individuals. Proficiency in imparting educational content to learners is a prerequisite for fulfilling the responsibilities of this position. Hence, in order to optimize their function, an educator must possess comprehension of the four fundamental principles of education. These principles can serve as a framework for structuring educational endeavours within primary school settings. The purpose of this practise is to equip students with the necessary skills and abilities to acquire knowledge in a more comprehensive manner, encompassing cognitive, practical, personal, and social domains. The forthcoming community service initiative is scheduled to take place in June 2023, wherein a cohort of 24 individuals will be engaged in the provision of educational instruction at the Nasyatul Aisyiyah Mungka Kindergarten.